Hybrid Models with Technology: Is it Effective for Learning in Abnormal Situations? - Purba, Ramen Antonov (LPPM Undiksha, 2022)
This study aims to analyze the effectiveness of hybrid model. Researcher will see blended learning with problem-based learning and whether Sevima EdLink can improve learning outcomes and problem-solving capabilities. Research quasi-experimental design are used in this study. Research conduct with total population of 4th-semester students is around 54 students. They are collecting data using question fields and exams. Analysis using t-test. They were followed by normality tests, homogeneity, and hypothesis. The finding of this research are learning with the hybrid model is going well. Blended learning with problem-based learning and Sevima EdLink runs on a reasonable classification composition. There was a very positive and contextual effect of combining blended learning with problem-based learning and Sevima EdLink on learning outcomes. There was also a very positive and contextual effect of combining blended learning with problem-based learning and Sevima EdLink on problem-solving capabilities. Research also shows that combining blended learning with problem-based learning and Sevima EdLink is reasonable and appropriate for use in abnormal learning situations.